Analysis of seismic microzonation and earthquake-induced building damage in Hatay: evidence from the February 6th, 2023, Earthquakes - Bingol, Hatice Buse; Sakarya, Adem; Akin, Oya (SPRINGER, 2025)
Two major earthquakes centered in Kahramanmara & scedil; struck T & uuml;rkiye on February 6th, 2023, that affected a vast area spanning 11 cities. Hatay was one of the cities that experienced the most severe damage. This study aims to investigate the extent to which the seismic microzonation map, based on local geological characteristics, influenced building damage in the study area covering the district centers of Antakya and Defne in Hatay. Five hazard themes, including the peak ground acceleration, site classification, site amplification, predominant period, and liquefaction potential, are used to produce the seismic microzonation map. It is produced by applying the criteria importance through intercriteria correlation and multinomial linear regression methods. Also, the multinomial logistic regression model is utilized to analyze the effect of seismic microzonation on building damage. The results indicate that seismic microzonation explains the building damage partially, and the hazard themes exert varying levels of effects on building damage. These results indicate that earthquake damage is affected not only by geological structure but also by other factors.
Keywords: Seismic microzonation; Kahramanmara & scedil; earthquakes 2023; Earthquake-resilient; Seismic hazard index; Earthquake damage; MULTINOMIAL LOGISTIC-REGRESSION; SIKKIM-HIMALAYA; GIS; VULNERABILITY; PARAMETERS; CITY; Geology; Meteorology & Atmospheric Sciences; Water Resources